ANALISIS TERHADAP PENYELESAIAN PEMBIAYAAN BERMASALAH PADA PERUSAHAAN PEMBIAYAAN ASTRA CREDIT COMPANY DI MEDAN (STUDI PADA PT ASTRA CREDIT COMPANY CABANG MEDAN) - CAROLLA SEMBIRING (PREMISE LAW JURNAL, 2017)
ABSTRACT A contract is a legal act which is in line with the formalities of the prevailing rules, depending upon the agreeing statement of the wish of two or more parties other party’s burden or for the sake of the interest of and on the burden of each party mutually. The result of the research showed that some factors which cause problematic financing were economic factor, the complaint of fraud by a debtor, deptor character, and the priority of other urgent uses. When a problematic financing occursuch as the case of Said Fahli, PT Astra Credit Company (ACC), Medan branch would take actions by intern solution, followed by the solution by Astra Credit Company (ACC) Jakarta. Some abstacles in solving problematic finance are deptors good faith, debetor’s complaint about the execution of fiduciary collateral, complaint about the sale price of fiduciary collateral, and the vehicle is in the hand of the third party. It is recommended that in other to decrease the factors which cause the debtor’s problematic financing related to his character (good faith), Astra Credit Company (ACC) should make stricter the analysis which is related to thedebtor’s data and make cross-check with those who know the debror well. It is also recommended that persuasive approach should be given the priority in order to know the factors which cause the debtor not to be able to take his responsibility to pay off his debt. In solving the problems, the company should be guided by the prevailing rules, especially by fiduciary collateral law. Keywords: Analysis of the Solution of Problematic Financing at PT Astra Credit Company